Heuristic-systematic processing of environmental messages: promoting green initiatives to Colorado ski resort visitors - Stonehouse, Taylor, author; Christen, Cindy, advisor; Lacy, Michael, committee member; Champ, Joseph, committee member (Colorado State University. Libraries, 2010)
This study examined the effects of environmental advertising by Colorado ski resorts on individuals' decisions to ski at those resorts. By applying Chaiken’s (1987) Heuristic Systematic Model of Persuasion and Dunlap and Van Liere’s (1978) New Environmental Paradigm, the researcher attempted to investigate an individual’s cognitive processes, along with the effects of their preexisting levels of environmental concern, when processing ski resort advertisements emphasizing environmental initiatives. A survey questionnaire was distributed to a convenience sample of 578 visitors at the Buttermilk resort (of Aspen Skiing Company), which is a company with many environmental initiatives; and Crested Butte Mountain Resort and Copper Mountain Ski Resort, which are companies with fewer environmental initiatives. After responding to questions regarding environmental concerns from the NEP scale, participants were exposed at random to one of three experimentally manipulated ski resort advertisements, which contained the same design, photographs and resort logos. However, messages were manipulated to emphasize environmental initiatives, affordability, or a mixture of the two messages. This study found that after exposure to an environmental advertisement, participants with high levels of environmental concern were found to be no more likely to list the environmental message before the heuristic cues. Consistent with the HSM, however, this study’s results indicated that participants with low environmental concern were more likely to remember the heuristic cues than the environmental message. Participants with higher levels of environmental concern were found to remember the environmental messages before the heuristic cues in the mixed advertisement, but no significant relationship was found between participants’ levels of environmental concern and the order in which they recalled the items from the different advertisements. Finally, this study found that participants with higher levels of environmental concern indicated that they were more likely to return to a resort after exposure to an advertisement promoting the resort’s environmental efforts. These results together illustrate the importance of a person’s motivation to scrutinize environmental advertisements. Furthermore, the location and complexity of these advertisements are key considerations for ski resorts wanting to promote their environmental efforts.
Covers not scanned.
Keywords: Green marketing -- Colorado; Ski resorts -- Colorado